Enhanced electrochemical performance and thermomechanical stability of nafion/sulfonated clay-carbon nanotube nanocomposite membranes for high-performance fuel cells under challenging conditions - Isabella Nicotera; Muhammad Habib Ur Rehman; Valeria Loise; Martina De Bonis; Coppola Luigi; Cataldo Simari (Materials for Renewable and Sustainable Energy)
Abstract The development of high-performance proton exchange membranes (PEMs) is crucial for advancing fuel cell technology, particularly under demanding operating conditions. This study investigates novel nanocomposite membranes based on Nafion reinforced with sulfonated clay-carbon nanotubes (sCC) as a hybrid filler. The incorporation of sCC not only improved the ion exchange capacity and hydrolytic stability but also critically modulated water dynamics, leading to superior water retention and sustained proton diffusion, particularly at elevated temperatures. The nanocomposite membranes exhibited substantially higher proton conductivity, especially under low relative humidity conditions, a critical factor for high-temperature fuel cell operation. Electrochemical evaluation in a H2/O2 direct hydrogen fuel cell (DHFC) showed an almost fourfold increase in peak power density (443.2 mW cm⁻²) under challenging high-temperature, low-humidity conditions (120 °C, 20% RH) for N-sCC-L3 compared to recast Nafion (117.3 mW cm⁻²).